Aktualisasi Transgender di Kabupaten Jombang - Wening Purbatin Palupi Soenjoto (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2016)
Transgender phenomena in the community get a variety of reactions. Many cases have sprung up that need to be addressed. In this study focused on the opinions and forms of social action carried out by a student against transgender existence. To answer the researchers used the theory of social action, Max Weber. Snowball is a technique used to determine the informant with the help to the informant. This research was conducted by means of qualitative description and choose a location in the area of Jombang, East Java. Data collected by means of in-depth interviews were then analyzed inductively. Based on the results of the study, presented on the causes being a transgender. Researchers found a uniform answer as to the cause of both informants about being transgender subjectively. It can be seen that transgender is a person were has a biological disorder for example born with two genitals and some were caused by some external factors as the influence of the social environment. In addition there are internal factors that have an instinct that is different from the original gender.